Pengaruh Gaya Kepemimpinan dan Stres Kerja Terhadap Kinerja Pegawai dengan Kepuasan Kerja Sebagai Variabel Intervening pada KPP Madya Dua Semarang - Sulistiawan, Agus; Budiati, Yuli; Kusnilawati, Nunik (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2024)
The research we conducted has the aim of examining the effect of Leadership Style and Work Stress on the performance of employees of KPP Madya Dua Semarang, and using job satisfaction as an intervening variable.This research is included in quantitative research with explanatory research type, by distributing questionnaires in the form of open and closed questions to employees of KPP Madya Semarang Dua as many as 112 people. The analysis technique used in this research is Partial Least Square-Structural Equation Modeling (PLS-SEM) with the SmartPLS approach.The results of this study indicate that job satisfaction can mediate two independent variables, namely Leadership Style and Work Stress. In addition, leadership style has a significant direct effect on employee performance, while work stress has no direct effect on employee performance.